The Influence of Fundamental and Macroeconomic Analysis on Stock Price - Adindah Novihartina Jafar (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
Investments that provide quite promising returns are stock investments. To see whether stocks can be profitable or not, simply investors often look in terms of changes in stock prices. The purpose of this study is to analyze the effect of fundamental and macroeconomic analysis on stock prices. Fundamental analysis is measured by return on assets (ROA), current ratio (CR), and debt to equity ratio (DER), while macroeconomic analysis is measured by inflation and interest rates. The data used in this study is secondary data in the form of company financial reports indexed by LQ45 for the 2018-2022 period. This study uses multiple linear regression analysis. The results showed that from the fundamental factors, the ROA variable had a positive and significant effect on the stock price of the LQ45 index. Meanwhile, the CR and DER variables don't affect the stock price of the LQ45 index. From macroeconomic factors, namely inflation and interest rates, they don't affect the stock price of the LQ45 index. Simultaneously the variables ROA, CR, DER, Inflation, and Interest Rates don't affect the stock price of the LQ45 index.